Teoretyczne aspekty planowania strategicznego w przedsiębiorstwach przemysłowych w warunkach współczesnych - Wojtołowski, Nikołaj W.; Gontarenko, J. W. (Theoretical Aspects of Strategic Planning of Industrial Companies in Contemporary Conditions, 2008)
The paper draws attention to the necessity of basing strategic planning on key competences. So far the industry structure based on resource and military sectors made such an approach difficult. The changes happening in the economy should allow the development of strategic planning in companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 425-428